The communication and satisfaction of the external client from the quality management system in the Aqueduct and Sewer System of Villavicencio, E.S.P. by Lida Basallo - Greis Mosquera - Juan Carlos Leal (GEON Journal (Management, Organizations and Business), 2015)
In this paper the relationship between the external client Water and Sewerage Company and feedback it has with the client described , considering the Colombian technical standard ISO 9001: 2008 specifically paragraphs 7.2.3 Customer Communication, 8.2.1 customer Satisfaction, performing a diagnostic entity , analyzing customer perception through the survey of user satisfaction survey and external clients in the development of work , allowing identify situations that hinder communication with the client, determine the means of most used between the client and the company and propose actions to improve the communication entity .
Keywords: Complaints; Claims; Level of user satisfaction; System Quality Management